2021
DOI: 10.1038/s41586-021-03462-x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous atmospheric production of organic acids mediated by cloud droplets

Abstract: Atmospheric acidity is increasingly determined by carbon dioxide and organic acids1–3. Among the latter, formic acid facilitates the nucleation of cloud droplets4 and contributes to the acidity of clouds and rainwater1,5. At present, chemistry–climate models greatly underestimate the atmospheric burden of formic acid, because key processes related to its sources and sinks remain poorly understood2,6–9. Here we present atmospheric chamber experiments that show that formaldehyde is efficiently converted to gaseo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
128
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(160 citation statements)
references
References 54 publications
9
128
5
Order By: Relevance
“…Although this underestimation of the model results is less apparent compared to that of the total column observations, it must be noted that only a limited number of merged data (53, see Table 2) is available for the comparison with aircraft observations and therefore such a comparison provides only an indication rather than a quantitative estimate. It must be stressed that Franco et al (2021) showed the importance of in-cloud chemistry for this tracer, which is missing in this study. The lack of adequate in-cloud chemistry would therefore explain the almost ubiquitous underestimation of this tracer.…”
Section: Hcoohmentioning
confidence: 63%
See 3 more Smart Citations
“…Although this underestimation of the model results is less apparent compared to that of the total column observations, it must be noted that only a limited number of merged data (53, see Table 2) is available for the comparison with aircraft observations and therefore such a comparison provides only an indication rather than a quantitative estimate. It must be stressed that Franco et al (2021) showed the importance of in-cloud chemistry for this tracer, which is missing in this study. The lack of adequate in-cloud chemistry would therefore explain the almost ubiquitous underestimation of this tracer.…”
Section: Hcoohmentioning
confidence: 63%
“…On the other hand, the large model versus observations differences in Southeast Asia also point to missing emissions from biomass burning. Finally, in-cloud chemistry could be important in the CH 3 COOH formation, analogously to formic acid (Franco et al, 2021), and this process could bring model results and observations to a closer agreement.…”
Section: Ch 3 Coohmentioning
confidence: 87%
See 2 more Smart Citations
“…They come from their dissolution from the gas and particulate phases or result from chemical transformations from organic precursors in the aqueous phase (Rose et al, 2018). For 400 example, the oxidative processing of aldehydes leads to the formation of carboxylic acids (Ervens et al, 2013;Franco et al, 2021) that can contribute to "aqSOA".…”
Section: Carboxylic Acidsmentioning
confidence: 99%